Financial Restructuring and Resolution of Banks - Colliard, Jean-Edouard; Gromb, Denis (Review of Financial Studies, 2025)
How do resolution frameworks affect the private restructuring of distressed banks? We model a bank’s shareholders and creditors negotiating a restructuring, under two frictions: asymmetric information about asset quality and externalities on the government. High-quality banks signal themselves by delaying the negotiation, which is socially inefficient. Public policies can improve welfare if they reduce the signaling motive or increase the negotiation surplus. Stricter bail-in rules make debt more information sensitive and increase delays. The bank chooses a capital structure with too little renegotiable debt, giving a new rationale, for example, for Total Loss Absorbing Capacity requirements.